2013
DOI: 10.1021/nn4034234
|View full text |Cite
|
Sign up to set email alerts
|

Solution-Processed Zinc Phosphide (α-Zn3P2) Colloidal Semiconducting Nanocrystals for Thin Film Photovoltaic Applications

Abstract: Zinc phosphide (Zn3P2) is a promising earth-abundant material for thin film photovoltaic applications, due to strong optical absorption and near ideal band gap. In this work, crystalline zinc phosphide nanoparticles are synthesized using dimethylzinc and tri-n-octylphosphine as precursors. Transmission electron microscopy and X-ray diffraction data show that these nanoparticles have an average diameter of ∼8 nm and adopt the crystalline structure of tetragonal α-Zn3P2. The optical band gap is found to increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
89
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(97 citation statements)
references
References 94 publications
8
89
0
Order By: Relevance
“…Two solvothermal synthetic strategies for crystalline Zn 3 P 2 nanospheres with different sizes are described in Figure c. Apparently, the advent of P(SiMe 3 ) 3 as the assisted phosphorus source realized the bigger Zn 3 P 2 nanospheres with diameter of ≈15 nm via a lower temperatures of 150 °C and shorter reaction time of 1 h. It was reasonable that phosphido‐bridged dimeric Zn(II) intermediates caused a compact linkage of metal‐phosphorus, rather than the metallic zinc species . Very recently, organism phytic acid (PA) as a principle phosphorus material was adopted to form TMPs.…”
Section: Synthesis Of Earth‐rich Transition Metal Phosphidesmentioning
confidence: 99%
“…Two solvothermal synthetic strategies for crystalline Zn 3 P 2 nanospheres with different sizes are described in Figure c. Apparently, the advent of P(SiMe 3 ) 3 as the assisted phosphorus source realized the bigger Zn 3 P 2 nanospheres with diameter of ≈15 nm via a lower temperatures of 150 °C and shorter reaction time of 1 h. It was reasonable that phosphido‐bridged dimeric Zn(II) intermediates caused a compact linkage of metal‐phosphorus, rather than the metallic zinc species . Very recently, organism phytic acid (PA) as a principle phosphorus material was adopted to form TMPs.…”
Section: Synthesis Of Earth‐rich Transition Metal Phosphidesmentioning
confidence: 99%
“…The most widely investigated quantum dots based on cadmium and lead chalcogenides (CdX and PbX where X=S, Se, Te) exhibit excellent performance in the solution processed photovoltaic devices by harvesting photon from visible to IR region . However, due to toxic nature of Cd and Pb extensive research is being carried out to synthesize the material which contains lesser toxic elements and have narrow band gap such as Bi 2 S 3 ,, FeS 2 , and Zn 2 P 3 …”
Section: Introductionmentioning
confidence: 99%
“…12,13 To date, there have been seven accounts of colloidal syntheses of Zn 3 P 2 . [14][15][16][17][18][19][20] The earliest study showed formation of zinc phosphide clusters with a distinct lowest energy excitonic transition (LEET) at 300 nm, indicative of relatively uniform crystalline particles, with an approximated 1 nm diameter. However, larger particles could not be obtained by this method.…”
mentioning
confidence: 99%